Penggunaan WhatsApp Chat untuk Mengajarkan Kemampuan Berbicara “Suggestion” dalam Muatan Kemaritiman pada Pembelajaran Online - Erna Pujiasih (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2023)
This study aims to obtain effective and efficient online learning activity so that students do not feel bored in learning during the COVID 19 pandemic. This article is a best practice which was conducted in the 1st semester, 2021-2022 academic year. The method in this study using qualitative descriptive. The subjects were the eleventh grade students of SMA N 1 Bantul which consists of 5 classes. The students can realize the importance of maintaining maritime. Indonesia is as an archipelagic country which consists of two-thirds of the ocean. Therefore, teachers in teaching English needs a strategy to foster a caring attitude towards maritime. Model of online learning aims to apply student speaking skills in the expression of